(untitled) (Intent Research Scientific Journal, 2023)
Irony is a powerful literary device that often serves as a vehicle for authors to convey their unique worldviews. The ability to convey complex ideas and themes through irony is a hallmark of English language fiction. In this article, we will delve into the works of Theodore Dreiser, a renowned American novelist of the early 20th century, and explore how irony is employed as a subtle but potent tool to express the author’s worldview. Dreiser’s works, marked by their realism and social commentary, provide an excellent lens through which to examine the nuanced role of irony in literature.